2012
DOI: 10.1016/j.ijpara.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Ookinete destruction within the mosquito midgut lumen explains Anopheles albimanus refractoriness to Plasmodium falciparum (3D7A) oocyst infection

Abstract: Graphical abstractHighlights► Development of a human malaria parasite is compared between two mosquito vector species. ► Ookinete formation within the midgut lumen is equivalent in both mosquito species. ► Plasmodium falciparum fails to produce oocyst infections in Anopheles albimanus. ► All ookinetes are destroyed within the midgut lumen of A. albimanus. ► Malaria parasite survival in all of the different midgut compartments is quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…Intriguingly, the activation of female gametocytes, fertilization, and generation of ookinetes were drastically reduced for PbATPβKO parasites in vivo (i.e., within the mosquito gut). The mosquito gut is a harsh environment for parasites (11,49), and the sole purpose of the highly motile ookinetes phase is to escape the gut and establish the new parasite generation in the insect hemocoel so it can produce sporozoites to accumulate in the salivary glands for transmission to new vertebrate hosts (35,50). Rescue experiments demonstrated that as little as 10 h in the mosquito gut was detrimental to ookinete viability in our PbATPβKO parasites.…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, the activation of female gametocytes, fertilization, and generation of ookinetes were drastically reduced for PbATPβKO parasites in vivo (i.e., within the mosquito gut). The mosquito gut is a harsh environment for parasites (11,49), and the sole purpose of the highly motile ookinetes phase is to escape the gut and establish the new parasite generation in the insect hemocoel so it can produce sporozoites to accumulate in the salivary glands for transmission to new vertebrate hosts (35,50). Rescue experiments demonstrated that as little as 10 h in the mosquito gut was detrimental to ookinete viability in our PbATPβKO parasites.…”
Section: Discussionmentioning
confidence: 96%
“…For example, both a laboratory P. falciparum line of putative African origin (NF54) and a clone from this line (3D7) have low infectivity in or fail to infect New World vectors such as A. albimanus and Anopheles darlingi (7,29). Furthermore, A. gambiae mosquitoes (African malaria vectors) are infected more efficiently with African P. falciparum isolates than with isolates from Thailand (37).…”
Section: Evidence Of Plasmodium Adaptation To Mosquito Vectorsmentioning
confidence: 99%
“…P. falciparum parasites are transmitted by more than 70 different anopheline species worldwide (3), but compatibilities differ between specific vector-parasite combinations (5). For example, P. falciparum NF54 (Pf NF54), of putative African origin, effectively infects Anopheles gambiae, the main malaria vector in sub-Saharan Africa; but A. albimanus is highly refractory to this strain (6)(7)(8); whereas Asian P. falciparum isolates infect Anopheles stephensi (Nijmegen strain), a major vector in India, more effectively than A. gambiae (9). Similar differences in compatibility have been reported between Plasmodium vivax and different anopheline species (10,11).…”
mentioning
confidence: 99%